2007
DOI: 10.1126/science.1135918
|View full text |Cite
|
Sign up to set email alerts
|

Predation Risk Affects Reproductive Physiology and Demography of Elk

Abstract: Elk (Cervus elaphus) in the Greater Yellowstone Ecosystem alter patterns of aggregation, habitat selection, vigilance, and foraging in the presence of wolves (Canis lupus). Antipredator behaviors like these can reduce predation risk but are also likely to carry costs. Data from five elk populations studied for 16 site years showed that progesterone concentrations (from 1489 fecal samples) declined with the ratio of elk to wolves. In turn, progesterone concentrations were a good predictor of calf recruitment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
413
4
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(427 citation statements)
references
References 8 publications
4
413
4
6
Order By: Relevance
“…Many of these adjustments can come at a cost to individual and population fitness because of a decrease in foraging time and/or because prey species are forced to forage in habitats with suboptimal forage availability, potentially reducing reproductive rates and affecting prey demography (Creel et al. 2007). Although smaller‐scale experimental studies have demonstrated strong and widespread effects of predation risk (e.g., Preisser et al.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these adjustments can come at a cost to individual and population fitness because of a decrease in foraging time and/or because prey species are forced to forage in habitats with suboptimal forage availability, potentially reducing reproductive rates and affecting prey demography (Creel et al. 2007). Although smaller‐scale experimental studies have demonstrated strong and widespread effects of predation risk (e.g., Preisser et al.…”
Section: Introductionmentioning
confidence: 99%
“…2001; Creel et al. 2007) with population effects potentially exceeding those of direct predation (Creel and Christianson 2008). It has been suggested that prey species may lose their antipredator behavior over time if predators disappear from the system (Sih et al.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding these consequences is important because they can enhance or obscure consumptive effects on prey population growth, life history, and resource use . Creel et al (2007) suggested that pregnancy rates of elk (Cervus elaphus) in the greater Yellowstone ecosystem, as determined indirectly through measurement of average fecal progesterone levels, decreased in the presence of wolves (Canis lupus). This apparent effect was attributed to changes in foraging patterns of elk that carried nutritional costs rather than changes in glucocorticoid concentrations due to stress (Creel et al 2009, Christianson andCreel 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the probability that elk are pregnant in mid-to late winter follows a logistic curve as a function of body fat (Cook et al 2004b). Thus, the hypothesized mechanism for lower pregnancy rates in elk as a consequence of antipredator responses that carry nutritional costs is that reduced body condition (fat, protein) results in (1) elk not conceiving due to low body fat during the autumn breeding season, (2) elk conceiv- ing but losing the fetus due to inadequate winter nutrition and inadequate progesterone levels to maintain pregnancy, or (3) some combination of both (Creel et al 2007(Creel et al , 2009). To prevent elk from accruing enough body fat to get pregnant, elk antipredator behavioral responses to wolves would have to result in limited forage intake or force elk into areas of lower forage quality during spring and summer.…”
Section: Introductionmentioning
confidence: 99%